2023
DOI: 10.3390/microorganisms11030746
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Gender and Sepsis—Implications for the Future

Abstract: Sex and gender dimorphisms are found in a large variety of diseases, including sepsis and septic shock which are more prevalent in men than in women. Animal models show that the host response to pathogens differs in females and males. This difference is partially explained by sex polarization of the intracellular pathways responding to pathogen–cell receptor interactions. Sex hormones seem to be responsible for this polarization, although other factors, such as chromosomal effects, have yet to be investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 123 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…Firm data for a biological connection between sex differences in clinical outcomes from animal models has been elusive. Previous studies on sepsis have generally supported better outcomes in female patients relative to male . This has been hypothesized to stem from the positive immunomodulatory properties of sex hormones on cell-mediated immune responses and cardiovascular functions in female patients as well as the suppression of the anti-infective response by testosterone in male patients .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Firm data for a biological connection between sex differences in clinical outcomes from animal models has been elusive. Previous studies on sepsis have generally supported better outcomes in female patients relative to male . This has been hypothesized to stem from the positive immunomodulatory properties of sex hormones on cell-mediated immune responses and cardiovascular functions in female patients as well as the suppression of the anti-infective response by testosterone in male patients .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on sepsis have generally supported better outcomes in female patients relative to male. 109 This has been hypothesized to stem from the positive immunomodulatory properties of sex hormones on cell-mediated immune responses and cardiovascular functions in female patients 110 , 111 as well as the suppression of the anti-infective response by testosterone in male patients. 112 Even an ongoing immunological advantage in postmenopausal septic women has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We found no statistically significant difference in the mortality rates for sepsis patients with CAD compared with those without CAD. Past studies have suggested that the prognosis of CAD and sepsis individually differs between male and female patients, [22][23][24][25] which led us to investigate sex as a variable for comparing mortality rates between ASHD CAD and non-ASHD groups. However, there was no disparity found in the mortality rates for male or female patients from either group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to acknowledge certain limitations in our study. One limitation is the exclusive use of male rats, which was a decision based on avoiding the potential interference introduced by the estrous cycle in female rats ( Lakbar et al., 2023 ). The study also had an observational nature without interventions to demonstrate the functional impact of microbial translocation.…”
Section: Discussionmentioning
confidence: 99%